Tattoo as a Possible Trigger for Autoimmune Syndrome Induced by Adjuvants (Global Journal of Medical Research, 2021)
Autoimmune/Inflammatory Syndromes Induced by Adjuvants (ASIA) syndrome is a group of immune-mediated disorders and symptoms that may appear in genetically predisposed individuals after environmental exposure to external factors, the adjuvants, such as silicone, aluminium and other metals. Sarcoidosis, one of its classic examples, have been previously described following tattoo. However, tattoo ink is still not recognized as one of the adjuvants capable of triggering the ASIA syndrome. To reinforce our theory, we also described a 32-yearold patient that developed arthralgia, sicca syndrome, small fiber neuropathy, and post orthostatic tachycardia syndrome (POTS) after being exposed to extensive areas of tattoos and propose the tattoo ink as a possible trigger for the ASIA syndrome, questioning its safety in individuals genetically prone for autoimmunity.
Keywords: tattoo; autoimmune/autoinflammatory syndrome induced by adjuvants; autoimmunity; autoantibodies; ink